2015
DOI: 10.18295/squmj.2015.15.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Perceptions of Peer Assessment in a Problem-based Learning Curriculum

Abstract: Objectives: Peer assessment (PA) is believed to support learning and help students develop both professionally and personally. The aim of this study was to examine medical students' perceptions of intragroup PA in a problem-based learning (PBL) setting. Methods: This study was carried out between September and November 2014 and involved six random groups of fourth-year undergraduate medical students (n = 60) enrolled at the Arabian Gulf University in Manama, Bahrain. While working on set tasks within a curricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Papinczak and colleagues found that peer assessment strengthened the sense of responsibility that group members had for each other, in which several students were enthusiastic and committed to providing helpful and valid feedback to support the learning of their peers [33]. In addition, studies by Tayem and colleagues and Zgheib and colleagues reported improvements in communication skills, professionalism, and ability to work on a team [40, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Papinczak and colleagues found that peer assessment strengthened the sense of responsibility that group members had for each other, in which several students were enthusiastic and committed to providing helpful and valid feedback to support the learning of their peers [33]. In addition, studies by Tayem and colleagues and Zgheib and colleagues reported improvements in communication skills, professionalism, and ability to work on a team [40, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Several qualitative studies and reviews from different corners of the world have reported similar concerns that engagement of students in curriculum development is of great importance in the sense that it will increase their interest in studies. 14,15,16,17,18 Our study results also reveals that by engaging the students in curriculum development would increase their interest in studies, the international studies also suggested that in order to enhance learning, engagement of students in the process of curriculum development is must. 19,20 The students become more active and can get good results.…”
Section: Increased Interest Of Students In Studiesmentioning
confidence: 61%
“…Moreover, this study reports students’ perceptions. Based on our previous work, we have reasonable evidence to believe that self‐assessment and peer evaluation are valid indicators. Nevertheless, the effectiveness of this intervention in terms of students’ performance in real‐world prescribing needs to be determined.…”
Section: Limitationsmentioning
confidence: 88%